2015
DOI: 10.1038/leu.2015.36
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of imatinib in CML over a period of 10 years: data from the randomized CML-study IV

Abstract: Tyrosine kinase inhibitors (TKI) have changed the natural course of chronic myeloid leukemia (CML). With the advent of second-generation TKI safety and efficacy issues have gained interest. The randomized CML - Study IV was used for a long-term evaluation of imatinib (IM). 1503 patients have received IM, 1379 IM monotherapy. After a median observation of 7.1 years, 965 patients (64%) still received IM. At 10 years, progression-free survival was 82%, overall survival 84%, 59% achieved MR(5), 72% MR(4.5), 81% MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
194
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(200 citation statements)
references
References 47 publications
5
194
0
1
Order By: Relevance
“…The CML annual incidence rate in China was 0.36/10 million people in 1992, which was decreased compared with that in Western countries (9). The first generation of tyrosine inhibitor imatinib as a first-line treatment of patients with CML is associated with a 10-year survival rate of 85-90% (10). To the best of our knowledge, the literature reports only 1 case of CML in a patient exhibiting SIT; the patient was a 69-year-old male exhibiting chronic granulocytic leukemia and SIT, which had induced a right-sided splenomegaly that was originally diagnosed as a hepatomegaly (11).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The CML annual incidence rate in China was 0.36/10 million people in 1992, which was decreased compared with that in Western countries (9). The first generation of tyrosine inhibitor imatinib as a first-line treatment of patients with CML is associated with a 10-year survival rate of 85-90% (10). To the best of our knowledge, the literature reports only 1 case of CML in a patient exhibiting SIT; the patient was a 69-year-old male exhibiting chronic granulocytic leukemia and SIT, which had induced a right-sided splenomegaly that was originally diagnosed as a hepatomegaly (11).…”
Section: Introductionmentioning
confidence: 97%
“…After 3 days of treatment with imatinib mesylate (600 mg/day) the WBC count of the patient had increased to 5.083x10 10 /l, at which point the imatinib mesylate treatment was replaced by the continuous intravenous infusion of cytarabine (200 mg/m 2 day). After 2 days of cytarabine treatment, the WBC count had decreased to 1.7x10 10 /l and the previous relevant symptoms were no longer present.…”
Section: Case Reportmentioning
confidence: 99%
“…Neither bosutinib nor ponatinib has been approved for the frontline treatment of CML-CP, [32,33] although some frontline clinical trial data are available for each. [34,35] Deep molecular responses to TKI therapy [37,38] however, imatinib 800 mg daily is not an approved treatment dose for patients with CML-CP. [39] Although a similar length of follow-up has not been reported for second-generation TKIs, frontline trials of second-generation TKIs versus imatinib showed that patients achieved deeper molecular responses with second-generation TKIs, and they achieved such responses more rapidly [29][30][31][40][41][42][43] (Table 1 Bosutinib and ponatinib are not approved for frontline treatment of CML-CP; however, data from their respective frontline clinical trials, while limited, suggest that many patients may be able to achieve deep molecular responses on these agents as well.…”
Section: Introductionmentioning
confidence: 99%
“…1 High-risk patients account for 10% to 25% of newly diagnosed CP CML patients, depending on which risk score is used, but even using Sokal, which is less selective and includes many more patients than Euro, European Treatment Outcome Study (EUTOS), and the new EUTOS long-term survival score, 14 the outcome of these patients is inferior, with a reported survival of 83%-89% at 5-6 years and of 68% at 10 years 7,10 (Table 1). In addition, the presence of clonal chromosome abnormalities in Ph+ cells (CCA/Ph+) at baseline, which occurs in 3% to 4% of patients, is a marker of an inferior outcome.…”
mentioning
confidence: 99%
“…1 Although the number of studies is limited, and the follow up is short and sometimes defective, survival data are substantial; around 90% at 5 years, 89% at 6 years, 86% at 8 years, and 83-84% at 10 years [2][3][4][5][6][7][8][9][10] (Table 1). Only 50% of deaths are due to the progression of leukemia, while 50% occur in remission and are due to other causes which occasionally include treatment-related toxicity and related complications.…”
mentioning
confidence: 99%